Fecal indicator bacteria, fecal source tracking markers, and pathogens detected in two Hudson River tributaries. (15th March 2020) - Brooks, Yolanda M.; Spirito, Catherine M.; Bae, Justin S.; Hong, Anna; Mosier, Emma M.; Sausele, Desiree J.; Fernandez-Baca, Cristina P.; Epstein, Jennifer L.; Shapley, Dan J.; Goodman, Laura B.; Anderson, Renee R.; Glaser, Amy L.; et al.
Abstract: Volunteer monitoring in the Hudson River watershed since 2012 has identified that the Wallkill River and Rondout Creek tributary complex have elevated concentrations of the fecal indicator bacteria, enterococci. Concentrations of enterococci do not provide insight into the sources of pollution and are imperfect indicators of health risks. In 2017, the regular monthly volunteer monitoring campaign for culturable enterococci at 24 sites on the Wallkill and Rondout expanded to include: (1) culturable measurements of E. coli and quantification of E. coli and Enterococcus specific markers vis nanoscale qPCR, (2) microbial source tracking (MST) assays (avian, human, bovine, and equine) via real time PCR and nanoscale qPCR, and 3) quantification of 12 gastrointestinal pathogens including viruses, bacteria, and protozoa via nanoscale qPCR. Three human associated MST markers (HumM2, HF183, and B. theta) corroborated that human pollution was present in Rondout Creek and widespread in the Wallkill River. The presence of B. theta was associated with increased concentrations of culturable E. coli. Genes for adenovirus 40 and 41 conserved region, rotavirus A NSP3, E. coli eae and stx1, and Giardia lamblia 18S rRNA were detected in >45% of samples. Abundance of rotavirus A NSP3 genes was significantly correlated to the bovine marker gene, CowM3, though wild bird sources cannot be ruled out. This is the first study to investigate potential fecal pollution sources and pathogen concentrations in Hudson tributaries during the months of peak recreational use. Graphical abstract: Image 1 Highlights: Bird fecal pollution is widespread in both the Wallkill River and Rondout Creek. Human fecal pollution was widespread in the Wallkill and detected in Rondout. Nanoscale qPCR highlighted the recurrence of diarrheal pathogens in the Wallkill. Rotavirus was the most abundant and consistently observed pathogen in the Wallkill.